Anthomyiidae, Fanniidae and Muscidae (Diptera) from the Juan Fernández Archipelago (Chile): 60 years after Willi Hennig’s contributions - Gomes, Lucas R. P.; Couri, Márcia S.; de Carvalho, Claudio J. B. (Zootaxa, 2018)
Sixty years ago, Willi Hennig last catalogued the Anthomyiidae, Fanniidae and Muscidae fauna of the Juan Fernández Archipelago. This archipelago, composed of three main volcanic islands (Robinson Crusoe, Alejandro Selkirk and Santa Clara), has many endemic species. We describe Fannia hennigi sp. n. from the Robinson Crusoe Island, and record 11 species in 10 genera of Anthomyiidae, Fanniidae and Muscidae. A key to the identification of all species found in Juan Fernández Archipelago and a table with all species found in the Archipelago are presented, including four new records from Robinson Crusoe Island: Delia platura (Meigen, 1826); Fannia hennigi sp. n.; Lispoides insularis Hennig, 1957 and Schoenomyzina emdeni Hennig, 1955.